2010
DOI: 10.1542/peds.2009-2920
|View full text |Cite
|
Sign up to set email alerts
|

Blood Sampling Through Peripheral Venous Catheters Is Reliable for Selected Basic Analytes in Children

Abstract: PVC sampling was shown to be a pain-reducing method that can be used for children for selected basic analytes. The findings for glucose were unreliable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…the researches of Zlotowski et al, as our study showed that there were statistically significant differences between the amount of potassium in blood samples taken from the peripheral vein catheter and vein puncture, but in contrast to our study, there were no significant differences between the amounts of sodium in the samples 8 . also Berger's study, Himberger's study 17,20 , Mohler's study (that was performed to examine the reliability of the blood samples were taken through peripheral intravenous infusion lines, saline lock and vein puncture from 55 patients for complete blood count and electrolytes in 1998) 21 , and Watson's study (that performed to compare the laboratory results of blood samples that were taken from the peripheral intravenous infusion line after was stopped the infusion fluids for 2 minutes with blood samples were taken from the opposite patient's arm in 1983) 13 , were contrast with our results in terms of sodium and potassium.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…the researches of Zlotowski et al, as our study showed that there were statistically significant differences between the amount of potassium in blood samples taken from the peripheral vein catheter and vein puncture, but in contrast to our study, there were no significant differences between the amounts of sodium in the samples 8 . also Berger's study, Himberger's study 17,20 , Mohler's study (that was performed to examine the reliability of the blood samples were taken through peripheral intravenous infusion lines, saline lock and vein puncture from 55 patients for complete blood count and electrolytes in 1998) 21 , and Watson's study (that performed to compare the laboratory results of blood samples that were taken from the peripheral intravenous infusion line after was stopped the infusion fluids for 2 minutes with blood samples were taken from the opposite patient's arm in 1983) 13 , were contrast with our results in terms of sodium and potassium.…”
Section: Discussionmentioning
confidence: 90%
“…Berger's study (that was performed on 47 children in 2004 to examine the possibility of replacing the common method of blood sampling with taking blood samples from peripheral intravenous infusion catheter) and himberger's study (that was performed on 64 patients to determine accuracy of results biochemical tests and complete blood count in samples that were taken from peripheral intravenous infusion catheters and by vein puncture in1998) and the results of researches of Zlotowskie's study & et al (to compare several experimental parameters from the analysis of blood samples which were obtained from Vein puncture and Saline Lock after injection of 200 ml of normal saline bolus on 30 patients in Emergency Department) similarly showed that there were no significant differences in terms of WBC, RBC, hemoglobin, hematocrit, and platelet contents, which were obtained by peripheral catheters and vein puncture 8,17,20 . These findings were consistent with our results in terms of all values, except for hemoglobin and hematocrit contents.…”
Section: Discussionmentioning
confidence: 94%
“…A considerable variation in haemolysis rates reported in the literature was identified. Seven studies reported a haemolysis rejection below 1% of all accessions [17][18][19][20][21][22][23], six between 1% and 3% [24][25][26][27][28][29], 20 between 3% and 20% [9,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and another four above 20% [49][50][51][52]. Haemolysis detection methods, and free plasma haemoglobin levels used for this detection, are likely to be partly responsible for this variation, in addition to the differences in study designs and study populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study by Berger-Achituv et al 23 showed that DVP and PVC results were not equivalent for glucose, although that study was performed on children and only 2 mL of blood were discarded before collection. A study by Zlotowski et al 20 also did not show equivalency for glucose, potassium and bicarbonate (not analysed in our study).…”
Section: Discussionmentioning
confidence: 99%